CLINICAL MANAGEMENT OF GENITAL PROLAPSE IN GRADED MURRAH BUFFALOES - A. Thangamani; K. Sunny Praveen; M. Srinivas; B. Chandra Prasad (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Pre and postpartum genital prolapse pose a threat to buffalo farmers and incur a financial loss in terms of milk loss and treatment costs. Effective clinical management warranted to treat the genital prolapse in field condition. In this context the present study was carried out to compare different therapeutic regimens for the management of genital prolapse in graded Murrah buffaloes. Buffaloe heifers (n=6) and She buffaloes (n=14) with a history of straining, discomfort, protruded posterior vagina and cervix through vulval lips were diagnosed with pre and postpartum genital prolapse. Depending on the severity of the prolapsed mass, either with or without oedema, different treatment modalities (finely powdered sugar, POP IN spray®, ice cubes, and herbal PROLAPSE IN powder®) were tested and were found to be effective without any complications.